Lipid nanoparticle technologies for nucleic acid delivery: a nanoarchitectonics perspective - Ferhan, Abdul Rahim (2022)
Lipid-based nanoparticles have emerged as a clinically viable platform technology to deliver nucleic acids for a wide range of healthcare applications. Within this scope, one of the most exciting areas of recent progress and future innovation potential lies in the material science of lipid-based nanoparticles, both to refine existing nanoparticle strategies and to develop new ones. Herein, the latest efforts to develop next-generation lipid-based nanoparticles are covered by taking a nanoarchitectonics perspective and the design, nucleic acid encapsulation methods, scalable production, and application prospects are critically analyzed for three classes of lipid-based nanoparticles: 1) traditional lipid nanoparticles (LNPs); 2) lipoplexes; and 3) bicelles. Particular focus is placed on rationalizing how molecular self-assembly principles enable advanced functionalities along with comparing and contrasting the different nanoarchitectures. The current development status of each class of lipid-based nanoparticle is also evaluated and possible future directions in terms of overcoming clinical translation challenges and realizing new application opportunities are suggested.